The scale dependency of trait‐based tree neighborhood models. (31st May 2020) - Zambrano, Jenny; Beckman, Noelle G.; Marchand, Philippe; Thompson, Jill; Uriarte, María; Zimmerman, Jess K.; Umaña, María N.; Swenson, Nathan G.
Abstract: Questions: We asked: (a) whether the strength of conspecific and heterospecific neighborhood crowding effects on focal tree survival and growth vary with neighborhood radii; and (b) if the relative strength of the effect of neighborhood interactions on tree growth and survival varies with neighborhood scale. Location: Luquillo Forest Dynamics Plot, Puerto Rico. Methods: We used tree survival and growth data and included information on species‐mean trait values related to several leaf traits, maximum height, seed mass and wood density. We incorporated a tree neighborhood modeling approach that uses an area around a focal tree with a specified radius, to describe the interactions between a focal tree and its neighbors. We constructed survival and growth models for each functional trait using a Bayesian approach, and varied the size of the radius from 5 m to 30 m, at 5‐m intervals. Results: The results suggested that the estimated effects of conspecific and heterospecific neighbors on tree performance do not vary based on the size of the neighborhood (5–30 m), suggesting that the effects of conspecific and heterospecific neighbors on the performance of a focal tree likely do not vary substantially beyond a neighborhood radius of 5 m in the Luquillo forest. In contrast, the estimated strength of the functional neighborhood (effect of neighbors based on their functional trait values) on tree performance was dependent on the neighborhood range. Our results also suggested that the effects of trait distances and trait hierarchies on tree survival and growth are acting simultaneously and at the same spatial scales. Conclusion: Findings from this study highlight the importance of spatial scale in community assembly processes, and specifically, call for increased attention when selecting the radius that defines the neighborhood around a focal tree as the selected neighborhood radius influences the community patterns discovered, and affects the conclusions about the drivers that control community assembly. Abstract : Neighborhood models have become popularized for studying drivers of tree community assembly. The models use an area around a focal tree with a specified radius to describe the interactions with close neighbors. Our results show that the choice of the neighborhood size is critical, as different radii may lead to very different conclusions on the drivers of community dynamics.